Benzophenone-3 and antinuclear antibodies in U.S. adolescents and adults ages 12-39 years - Parks, Christine G.; Meier, Helen C. S.; Jusko, Todd A.; Wilkerson, Jesse; Miller, Frederick W.; Sandler, Dale P. (Frontiers in Immunology, 2022)
Background: Between 1988 and 2012, prevalence of antinuclear antibodies (ANA) increased in the U.S., especially in adolescents and non-Hispanic Whites. Female predominance of ANA suggests a role for hormonal factors, including xenobiotic exposures that may disrupt endocrine signaling. Benzophenone-3 (BP-3) is one such chemical with increasing exposure through sunscreen use. We investigated whether urinary BP-3 levels were related to ANA in adolescents and young adults. Methods: In a sample of 1,785 individuals ages 12-39 years in the National Health and Nutrition Examination Survey (NHANES; 2003-4, 2011-12), we examined cross-sectional associations of ANA (N=192; 3+ or 4+ at the 1:80 dilution, measured by HEp-2 immunofluorescence) with urinary BP-3, and other phenols bisphenol-A, triclosan, and parabens. Adjusted prevalence odds ratios (POR) were calculated in season-stratified models [winter (November-April) and summer (May-October)], given differences in sunscreen use and BP-3 concentrations. Results: BP-3 concentrations (detected in >98.5% of individuals) did not differ by ANA positivity in the summer (geometric mean, GM 30.6 ng/ml ANA-positive vs. 35.3 ANA-negative; GM ratio 1.15), but in winter were higher among ANA-positives (50.2 vs. 20.1 ANA-negative; GM ratio 2.50). ANA was associated with log10BP-3 in winter (POR 1.57; 95%CI 1.07-2.30 per unit increase) but not summer (0.94; 0.61, 1.44; interaction p=0.09). Triclosan, parabens, and bisphenol-A levels were unrelated to ANA overall or by season (ORs 0.64 to 1.33). Conclusions: The association of urinary BP-3 with ANA in the winter may reflect different exposure patterns or unmeasured confounders. Findings warrant replication in prospective studies and including past and year-round exposures.